Saving Good Quality of Sleep for Cervical Herniated Nucleus Pulposus Patients - Ridha Dharmajaya (Neurologico Spinale Medico Chirurgico, 2018)
Background: Cervical herniated nucleus pulposus compresses the nerve roots with clinical pain manifestation and causes sleeping disturbances. The aim of this study was to determine the difference in the quality of sleep before and after surgery. Method: This is a retrospective cohort study. Patients were asked to complete the Pittsburgh Sleep Quality Index (PSQI) and all data was analyzed with the McNemar Test.Result: The outcome revealed that in 98 patients, 72 (73.4%) patients had increased their quality of sleep after surgery. Conclusion: There was a significant difference in the quality of sleep pre- and post-surgery.